Benzyl thioether formation merging copper catalysis. Issue 2 (23rd December 2021) - Xu, Bing; Lin, Ying; Ye, Yang; Xu, Li; Xie, Tian; Ye, Xiang-Yang
Abstract : A novel copper-catalyzed thioetherification reaction has been developed to afford benzyl thioethers in moderate to excellent yields. Abstract : A novel copper-catalyzed thioetherification reaction has been developed to afford benzyl thioethers in moderate to excellent yields. Under the mild and easy-to-operate conditions, a variety of thioethers are efficiently prepared from readily available benzyl alcohols (primary, secondary, and tertiary) and thiols in the presence of Cu(OTf)2 as the Lewis acid catalysis. This C–S bond formation protocol furnishes exceptional chemoselectivity, and the preliminary mechanism studies show that the reaction should proceed through a Lewis-acid-mediated SN 1-type nucleophilic attack of the carbocations formed in situ .